Teoretyczne i praktyczne ograniczenia implementacji zasad demokratycznych modelu deliberatywnego w Europie Środkowej na przełomie XX i XXI w. – uwagi in statu nascendi - Olbromski, Cezary Józef (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
This paper refers to the issue of the forming of societies in former satellite states of totalitarian communism, which turned to the democratic model of political decision- making and exercising authority. The paper is not strictly historical, although it is based on historical materials, nor is it a commentary on current political events. I am trying to show that the implementation of the representational principle in democratic systems of these states creates a loophole in the citizens’ competence and to a certain extent makes its applicability senseless. The citizens, who have so far been equal before the law, are now (theoretically) equal before their representatives. The latter represent concrete groups of citizens who should vote for them on the basis of an electoral system (constituency). The antidote to neutralize the consequences of this apory is provided by the principle of deliberativeness as the tool leading the forming society and its representatives to sovereign political decisions.